Breaking the tolerance for tumor: Targeting negative regulators of TLR signaling - Standiford, Theodore J. (Landes Bioscience, 2012)
Tumors arise and progress in immunocompetent hosts presumably by activating tolerance mechanisms critical for normal homeostasis. Host immune cells can mount anti-tumor responses by activation of Toll-like receptors (TLRs). However, emerging data suggests that molecules that negatively regulate TLRs are exploited by tumors to induce tolerance and mitigate the host immunosurveillance. Targeting these negative regulators can be a potential new immunotherapeutic strategy.